2023
DOI: 10.1021/acsomega.2c07480
|View full text |Cite
|
Sign up to set email alerts
|

Z-Guggulsterone Induces Cell Cycle Arrest and Apoptosis by Targeting the p53/CCNB1/PLK1 Pathway in Triple-Negative Breast Cancer

Abstract: Myrrh is the dried resin of Commiphora Myrrh Engl., which exerts anticancer properties. However, its effects and molecular mechanisms in triple-negative breast cancer (TNBC) remain unclear. In this study, we used network pharmacology to screen Z-Guggulsterone (Z-GS) as a characteristic active component of myrrh. Cell Counting Kit-8 proliferation assays showed that Z-GS inhibited proliferation of the TNBC cell lines MDA-MB-468 and BT-549. Transwell assays also showed that Z-GS inhibited TNBC migration and invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…This indicates the presence of significant differences in the specific compounds detected in each type of myrrh. For instance, the main components of Somali gum myrrh are trans-alpha-Bergamotene, beta-Bourbonene, Cyclohexane, and Germacrene D, while the main components of Somali natural myrrh are Naphthalene, 1,2,3,4,4a,5,6,8a-octahydro-4a,8-dimethyl-2-(1-methylethenyl)-, Cyclohexene and Germacrene D. The main components of grade A Kenyan natural myrrh are Cyclohexene and alfa-Copaene, while the main components of grade B Kenyan natural myrrh are Ethylene oxide and Cyclopenta [1,3]cyclopropa [1,2]benzene. The main components of grade A Kenyan vinegar-treated myrrh are Ethylene oxide and 1H-Cyclopenta [1,3]cyclopropa [1,2]benzene, while the main components of grade B Kenyan vinegar-treated myrrh are (1R)-2,6,6-Trimethylbicyclo[3.1.1]hept-2-ene and 2-methyl-5-(1-methylethyl)-.…”
Section: Gc-ms Analysis Results Of Myrrh Volatile Gasesmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates the presence of significant differences in the specific compounds detected in each type of myrrh. For instance, the main components of Somali gum myrrh are trans-alpha-Bergamotene, beta-Bourbonene, Cyclohexane, and Germacrene D, while the main components of Somali natural myrrh are Naphthalene, 1,2,3,4,4a,5,6,8a-octahydro-4a,8-dimethyl-2-(1-methylethenyl)-, Cyclohexene and Germacrene D. The main components of grade A Kenyan natural myrrh are Cyclohexene and alfa-Copaene, while the main components of grade B Kenyan natural myrrh are Ethylene oxide and Cyclopenta [1,3]cyclopropa [1,2]benzene. The main components of grade A Kenyan vinegar-treated myrrh are Ethylene oxide and 1H-Cyclopenta [1,3]cyclopropa [1,2]benzene, while the main components of grade B Kenyan vinegar-treated myrrh are (1R)-2,6,6-Trimethylbicyclo[3.1.1]hept-2-ene and 2-methyl-5-(1-methylethyl)-.…”
Section: Gc-ms Analysis Results Of Myrrh Volatile Gasesmentioning
confidence: 99%
“…Myrrh is the dry resin from Commiphora myrrha Engl. or Commiphora molmol Engl, which grows in arid regions of the Middle East, Africa, and Asia [1]. Myrrh has been widely used in traditional medicine for thousands of years for its anti-inflammatory, analgesic, antimicrobial, and antioxidant properties [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…30 Previous studies have indicated that p53 down-regulated the expression of CCNB1, and CCNB1 silencing inhibits cell proliferation and induces cell senescence via activation of the p53 signaling pathway. 31,32 The expression of CCNB1 was elevated in various cancers, and the high expression of CCNB1 was related to poor prognosis. 32,33 Recent research has also revealed that the expression of CCNB1 increased in human thoracic aortic dissection and the genetic variants in CCNB1 correlated with the risk of coronary in-stent restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin B1 (CCNB1) is a key factor in the initiation of mitosis, and CCNB1 can form complexes with CCNB2 and CDK1, thus regulating the G2/M phases of mammalian cell 30 . Previous studies have indicated that p53 down‐regulated the expression of CCNB1, and CCNB1 silencing inhibits cell proliferation and induces cell senescence via activation of the p53 signaling pathway 31,32 . The expression of CCNB1 was elevated in various cancers, and the high expression of CCNB1 was related to poor prognosis 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…The Cell Counting Kit-8 (CCK-8) (Topscience, Shanghai, China) was employed for determination of the muscone-based regulation of cell survivability. Approximately 4 × 10 3 cells were introduced to individual wells of 96-well plates, and plates underwent a 24 h-incubation at 37 °C and 5% CO 2 humid chamber [ 19 21 ]. Cells were exposed to several muscone concentrations followed by 24, 48, or 72 h incubation.…”
Section: Methodsmentioning
confidence: 99%